Oil, wine, and the cultural economy of ancient Greece - Pratt, Catherine E. (Cambridge, United Kingdom)
xiv, 409 sayfa
Keywords: “Chapter 1 Introduction “There are two liquids most pleasing to human bodies: inside-wine, outside-oil.“--Pliny (23-79 CE), Natural History XIV, 29.150 “It is evident that the country now called Hellas had in ancient times no settled population ... without commerce, without freedom of communication either by land or sea, cultivating no more of their territory than the exigencies of life required, destitute of capital, never planting their land ...“ -Thucydides (c. 460-400 BCE), History of the Peloponnesian War, 1.2.1-2 Oil, Wine, and Cultural History in Pre-Classical Greece This book aims to explore the centrality of olive oil and wine in various realms of ancient Greek life and how this interdependence came to exist and persist. Indeed, this book argues that oil and wine can be regarded not just as economic commodities, but cultural commodities that actively shaped the paths of ancient Greek history. Cultural commodities can be defined as things that have become deeply entangled with humans through increasing ties of dependency that are reinforced by a high value constructed within multiple contexts of exchange. On the one hand, expansions and contractions of dependencies between people and oil/wine can be seen by tracing shifting emphases in exchange modes-such as commensal, gift, and commercial exchange-within their social and environmental contexts over the long-term.” --